2017
DOI: 10.18632/oncotarget.16292
|View full text |Cite
|
Sign up to set email alerts
|

Lithium protects hippocampal progenitors, cognitive performance and hypothalamus-pituitary function after irradiation to the juvenile rat brain

Abstract: Cranial radiotherapy in children typically causes delayed and progressive cognitive dysfunction and there is no effective preventive strategy for radiation-induced cognitive impairments. Here we show that lithium treatment reduced irradiation-induced progenitor cell death in the subgranular zone of the hippocampus, and subsequently ameliorated irradiation-reduced neurogenesis and astrogenesis in the juvenile rat brain. Irradiation-induced memory impairment, motor hyperactivity and anxiety-like behaviour were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 62 publications
3
28
0
Order By: Relevance
“…Thus we used female rats as the irradiation animal model, and in this study we found that brain irradiation in juvenile female rats led to greater weight gain with age, particularly from 15 weeks after irradiation. Such a greater weight gain did not occur in our previous irradiation studies with male rats [4, 24]. With the aim of further characterizing the weight changes, we evaluated the BMI and abdominal circumference, and these two indicators also increased significantly with age in female rats after juvenile brain irradiation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus we used female rats as the irradiation animal model, and in this study we found that brain irradiation in juvenile female rats led to greater weight gain with age, particularly from 15 weeks after irradiation. Such a greater weight gain did not occur in our previous irradiation studies with male rats [4, 24]. With the aim of further characterizing the weight changes, we evaluated the BMI and abdominal circumference, and these two indicators also increased significantly with age in female rats after juvenile brain irradiation.…”
Section: Discussionmentioning
confidence: 84%
“…However, radiotherapy has both acute and long-lasting adverse effects that can result not only in intellectual impairment [3, 4], but also in endocrine and metabolic sequelae such as growth retardation and metabolic syndrome [5, 6]. Metabolic dysfunction is an increasingly recognized complication of childhood cancer treatments, and childhood cancer survivors are twice as likely as their siblings to be diagnosed with type 2 diabetes mellitus, hypertension, and dyslipidemia, and they have a 4-fold increase in mortality from cardiovascular disease as they enter adolescence and adulthood [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…The level of radiation-related cognitive impairment is influenced by multiple factors, such as the patient's age and the irradiated brain region may be the most important factors [22]. There is a large body of data showing that age is a risk factor for side effects of RT [30], and the effect on the developing adolescent brain is even more pronounced [31]. In addition, other studies have shown that exposure to different areas of the brain is not equally likely to cause the radiation-related cognitive impairment.…”
Section: Factors Influencing Radiation-related Cognitive Impairmentmentioning
confidence: 99%
“…Lithium, commonly used in the treatment of bipolar disorder, has been shown to exert neuroprotective and regenerative effects in a variety of neurological insults (Shorter 2009). In preclinical studies lithium protected the neonatal brain against the neurodegenerative effects of hypoxia-ischemia (HI) (Xie et al 2014) and rescued cognitive loss in adult as well as in young mice after cranial irradiation (Yazlovitskaya et al 2006) (Huo et al 2012;Zhou et al 2017). The neuroprotective effects of lithium after cranial radiation are attributable to enhanced hippocampal neurogenesis and decreased apoptosis in young rats and mice (Yazlovitskaya et al 2006) (Huo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These complications include late-occurring cognitive impairments, and a negative impact on social competence (Armstrong et al 2010;Georg Kuhn and Blomgren 2011). It has been demonstrated in animal models that preserving or promoting neurogenesis helps attenuate the cognitive deficits observed in irradiated mice and rats (Naylor et al 2008a;Zhou et al 2017). Progress has been made in identifying mechanisms underlying the neuroprotective effects of lithium in rodent models of brain injury, including anti-apoptotic effects (H. Li et al 2011) (Huo et al 2012) (Omata et al 2008;Q.…”
Section: Lithium Is Effective Even When Introduced Long After the Injurymentioning
confidence: 99%